Faktor Determinan Yang Mempengaruhi Kualitas Audit Internal Inspektorat Se-Eks Karesidenan Surakarta - Leni Mardayanti; Hudi Kurniawanto (CV. ITTC INDONESIA, 2024)
The purpose of this research is to determine the significance of the influence of work experience, professional ethics, and time budget pressure on the quality of internal audits with top management support as a moderating variable at the Surakarta Residency Inspectorate. The use of this research is as a consideration for making efforts to improve the quality of internal audits in each regional inspectorate office. The survey method was used in this research by collecting questionnaire data from auditors and P2UPD Inspectorates throughout the Surakarta Residency, which consists of seven inspectorates. The sampling technique used purposive sampling as many as 197 respondents. The data analysis technique uses moderated regression analysis. The research results show that work experience and professional ethics influence internal audit quality significantly positively, while time and budget pressure do not influence internal audit quality. Based on the MRA test on the moderating variable, the results showed that top management support did not moderate each independent variable on the dependent variable.